Primary Amebic Meningoencephalitis: What Have We Learned in the Last Five Years? - Cope, Jennifer R. (Curr Infect Dis Rep, 2016)
Primary amebic meningoencephalitis (PAM) is a devastating infection of the brain caused by the thermophilic free-living ameba, Naegleria fowleri. Infection can occur when water containing the ameba enters the body through the nose, usually during recreational water activities such as swimming or diving. Historically, in the United States, cases were mostly reported from the warmer southern-tier states. In the last five years, several notable changes have been documented in PAM epidemiology including a northward expansion of infections and new types of water exposures. The recent reports of two PAM survivors provide hope for improved outcomes with early diagnosis and aggressive treatment. Advanced molecular laboratory tools such as genome sequencing might provide more insight into the pathogenicity of Naegleria fowleri. Clinicians treating patients with meningitis and warm freshwater exposure are encouraged to consider PAM in their differential diagnoses.